2010
DOI: 10.1002/eji.200939724
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin suppresses airway inflammation independently of systemic Th1/Th2 immune modulation

Abstract: Oxidative stress plays an important role in the pathogenesis of asthma via the upregulation of local inflammatory mediators and/or promoting Th2-skewing during Ag sensitization. Thioredoxin (TRX), a 12 kDa redox-active protein with antioxidative property, has been recently shown to play a protective role in various inflammatory diseases. Using a mouse model of asthma, we show here that IL-13 and eotaxin production are decreased in TRX-Tg mice leading to reduced eosinophils recruitment and mucus metaplasia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
1
24
0
1
Order By: Relevance
“…Так, TRX 1 индуцирует экспрессию Th 1 -ассоциированных ци-токинов, обусловливает снижение реактивности и степени воспаления бронхиального дерева, пре-дотвращает развитие гиперплазии бокаловидных клеток, ингибируя экспрессию генов MUC и Gob-5 [11, 60,61]. TRX ингибируют продукцию фак-тора, подав ляющего макрофагальную миграцию (macrophage migration inhibitory factor), и эотаксина, тем самым ограничивая рекрутирование эозино-филов в слизистую оболочку бронхиальной стенки [59]. Показано, что PRX 1 , ингибируя продукцию IL-2, снижает активность Th 2 -ассоциированного воспалительного процесса в респираторном тракте [46].…”
Section: резюме в обзоре литературы изложены современные данные о спunclassified
“…Так, TRX 1 индуцирует экспрессию Th 1 -ассоциированных ци-токинов, обусловливает снижение реактивности и степени воспаления бронхиального дерева, пре-дотвращает развитие гиперплазии бокаловидных клеток, ингибируя экспрессию генов MUC и Gob-5 [11, 60,61]. TRX ингибируют продукцию фак-тора, подав ляющего макрофагальную миграцию (macrophage migration inhibitory factor), и эотаксина, тем самым ограничивая рекрутирование эозино-филов в слизистую оболочку бронхиальной стенки [59]. Показано, что PRX 1 , ингибируя продукцию IL-2, снижает активность Th 2 -ассоциированного воспалительного процесса в респираторном тракте [46].…”
Section: резюме в обзоре литературы изложены современные данные о спunclassified
“…Trx expression is upregulated in various pulmonary diseases, primarily in lung cancer (Fernandes et al, 2009;Park et al, 2006;Soini et al, 2001), pulmonary fibrosis and interstitial lung disease (Iwata et al, 2010;Tiitto et al, 2003), and COPD (Lehtonen et al, 2008), and increased extracellular levels of Trx have been reported in subjects with acute lung injury and asthma exacerbations (Callister et al, 2006;Yamada et al, 2003), indicating increased oxidative stress in these cases (Xu et al, 2012). Transgenic overexpression of Trx protects alveolar epithelial cells from hyperoxia-induced injury (Chen et al, 2010), is protective against bleomycin-induced injury (Hoshino et al, 2003), and suppresses allergic inflammation by a mechanism independent of Th1/Th2 immune modulation (Torii et al, 2010), and administration of recombinant Trx proteins has shown protective effects against various lung pathologies associated with oxidative stress (Nakamura et al, 2005).…”
Section: Other Redox Regulating Enzymesmentioning
confidence: 99%
“…In contrast, TRX-transgenic (Tg) mice showed levels of IFN-γ comparable to those in wild-type mice with inflammatory bowel disease [13]. Additionally, Torii et al [14] reported that although CD4+ T cells from both TRX-Tg mice and wild-type mice developed similar Th1 and Th2 responses, eosinophil recruitment and mucus metaplasia in the airways were reduced in TRX-Tg mice through a decreased production of macrophage migration inhibitory factor (MIF), which was produced by T cells as well as monocytes/macrophages and was an upstream modulator of allergic airway inflammation [15]. The conflict between these studies may also be related to variations in mice’s genetic background, immunization protocol, and cell type.…”
Section: Effect Of Trx In Allergic Inflammationmentioning
confidence: 99%
“…As a result, preincubation with TRX suppressed CCL-11 (eotaxin), which is also a selective chemoattractant, and RANTES-induced chemotaxis of eosinophils in the absence of Th1 or Th2 cytokines [17]. Additionally, Torii et al [15] found that there were significantly lower concentrations of eotaxin in the BALF of TRX-Tg mice, and they stated that TRX may be attributable to decreased inflammation and lung infiltration by eosinophils secondary to a decreased production of eotaxin. Thus, these data may indicate that TRX negatively regulates allergic airway inflammation by eosinophils indirectly through the suppression of Th2 cytokines as well as the downregulation of MIF production leading eotaxin production and directly through the inhibition of eosinophil chemotaxis (fig.…”
Section: Effect Of Trx In Allergic Inflammationmentioning
confidence: 99%